Therapeutic effectiveness of alternative medications in oral lichen planus: A systematic review - Vadivel, Jayanth Kumar (J Oral Maxillofac Pathol, 2020)
Lichen planus is a chronic inflammatory condition affecting the skin and mucosa. The etiology is unknown but the pathogenesis appears to be an immune-mediated reaction. The mainstay drugs used in the treatment are immunomodulators. The aim of this paper is to report on the therapeutic effectiveness of the alternate medications used in the management of oral lichen planus (OLP). A systematic search of PubMed, Web of Science and Cochrane Controlled Clinical trials were done for all the papers published until December 2019. The search resulted in a total of 20 studies that were found suitable for the review. The results showed that the reduction in pain, treatment effectiveness was comparable between the steroids and alternative medications. However, the alternative medications had a therapeutic advantage in studies that had used placebo as controls and the results were statistically significant (P < 0.05). No major adverse effects were reported with the usage of alternative medications. There is definitely a therapeutic potential in the usage of alternative medications in the management of OLP. In terms of therapeutic effectiveness, they are on par with the immunomodulators. These alternative medications offer us a new therapeutic option in the management of OLP without any adverse effects.